Implementasi Media Interaktif Wordwall Berbasis Model Problem Based Learning pada Pembelajaran Pendidikan Pancasila di Kelas V SD Negeri Gisikdrono 02 Semarang - Salsabila, Eliana Putri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the feasibility and effectiveness of using Wordwall interactive media based on Problem Based Learning (PjBL) in Pancasila Education subjects for class V students at SD Negeri Gisikdrono 02. This research is motivated by the low level of motivation and learning concentration among students in class. V SD Negeri Gisikdrono 02, Semarang City. Based on the results of observations made at this elementary school, specifically in class V at SD Negeri Gisikdrono 02, it can be seen that most students still do not show enthusiasm for their learning. So their motivation and concentration in learning decreases, especially in learning Pancasila and Citizenship Education due to a lack of instilling and implementing Pancasila values in the form of mutual cooperation between each other. Based on the results of the research that has been carried out, it can be concluded that learning Pancasila Education using the PjBL learning model or Problem Based Education can improve student learning outcomes.